Improved wetlands analytics for achieving the goals of both the Ramsar Convention and the Kunming-Montreal Global Biodiversity Framework for wetlands monitoring - Elena A. Mikhailova; Hamdi A. Zurqani; Lili Lin; Zhenbang Hao; Christopher J. Post; Mark A. Schlautman; Gregory C. Post; George B. Shepherd (Wetlands Ecology and Management, 2026)
Wetlands are an important part of the Ramsar Convention (RC) and Kunming-Montreal Global Biodiversity Framework (KM-GBF), which is a significant agreement committing 196 countries (the United States is not a participant of KM-GBF) to a reduction and halting of the loss of biodiversity by 2030. In comparison to the broadly focused KM-GBF, goals of RC (172 contracting parties) are wetlands-focused such as “wise use” and protection of wetlands, selection of wetlands of “international importance”, and international collaboration. The goal of this study is to explore how improved wetlands analytics can help achieve the goals of both the RC and KM-GBF using the state of North Carolina (NC) in the United States of America (USA) as an example. Several goals and targets of KM-GBF are applicable to wetlands, with only a handful of indicators (e.g., wetland extent trends (WET) index) to monitor them. The WET index is only relevant at the global or continental scale because it relies on a limited database of wetland sites over time. Unfortunately, the WET index does not allow tracking of smaller spatial extents and new methods are needed to understand how wetlands are changing over time. Geospatial analysis results and recommendations are presented for both RC and KM-GBF. Loss of wetlands can result in transboundary damage, harming biodiversity and ecosystem functions and services (ES). A case study of NC showed that almost 49% of the wetland area was lost between 1780 and 1980 in the state. Wetlands loss in NC continued between 2001 and 2021. Future RC and KM-GBF refinements could use sea level rise analysis to evaluate changes in wetlands.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Composition and distribution of the near-shore waters bordering the coral reefs of Aruba, Bonaire, and Curaçao in the Southern Caribbean - Fleur C. van Duyl; Vincent E.A. Post; Boris M. van Breukelen; Victor Bense; Petra M. Visser; Erik H. Meesters; Paul Koeniger; Mark J.A. Vermeij (Marine Pollution Bulletin, 2024)

Corrigendum to “Design and development of modular magnetic bio inspired autonomous underwater robot – MMBAUV” [Ocean Eng. 273 (2023) 113968] - Marvin Wright; Qing Xiao; Saishuai Dai; Mark Post; Hong Yue; Bodhi Sarkar (Ocean Engineering, 2024)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Design and development of modular magnetic bio-inspired autonomous underwater robot – MMBAUV - Marvin Wright; Qing Xiao; Saishuai Dai; Mark Post; Hong Yue; Bodhi Sarkar (Ocean Engineering, 2023)

More effective transposon regulation in fertile, long‐lived termite queens than in sterile workers - Frederik Post; Erich Bornberg‐Bauer; Mireille Vasseur‐Cognet; Mark C. Harrison (Molecular Ecology, 2023)
Transposable elements (TEs) are mobile genetic sequences, which can cause the accumulation of genomic damage in the lifetime of an organism. The regulation of TEs, for instance via the piRNA‐pathway, is an important mechanism to protect the integrity of genomes, especially in the germ‐line where mutations can be transmitted to offspring. In eusocial insects, soma and germ‐line are divided among worker and reproductive castes, so one may expect caste‐specific differences in TE regulation to exist. To test this, we compared whole‐genome levels of repeat element transcription in the fat body of female workers, kings and five different queen stages of the higher termite, Macrotermes natalensis . In this species, queens can live over 20 years, maintaining near maximum reproductive output, while sterile workers only live weeks. We found a strong, positive correlation between TE expression and the expression of neighbouring genes in all castes. However, we found substantially higher TE activity in workers than in reproductives. Furthermore, TE expression did not increase with age in queens, despite a sevenfold increase in overall gene expression, due to a significant upregulation of the piRNA‐pathway in 20‐year‐old queens. Our results suggest a caste‐ and age‐specific regulation of the piRNA‐pathway has evolved in higher termites that is analogous to germ‐line‐specific activity in solitary organisms. In the fat body of these termite queens, an important metabolic tissue for maintaining their extreme longevity and reproductive output, an efficient regulation of TEs likely protects genome integrity, thus further promoting reproductive fitness even at high age.

Future-proofing hydrogeology by revising groundwater monitoring practice - Gabriel C. Rau; Mark O. Cuthbert; Vincent E. A. Post; Daniel Schweizer; R. Ian Acworth; Martin S. Andersen; Philipp Blum; Elisabetta Carrara; Todd C. Rasmussen; Shemin Ge (Hydrogeology Journal, 2020)
Groundwater is an important global resource and its sustainable use faces major challenges. New methods and advances in computational science could lead to much improved understanding of groundwater processes and subsurface properties. A closer look at current groundwater monitoring practice reveals the need for updates with a special focus on the benefits of high-frequency and high-resolution datasets. To future-proof hydrogeology, this technical note raises awareness about the necessity for improvement, provides initial recommendations and advocates for the development of universal guidelines.

Celebrating 50 years of SWIMs (Salt Water Intrusion Meetings) - Vincent E. A. Post; Gualbert Oude Essink; Adam Szymkiewicz; Mark Bakker; Georg Houben; Emilio Custodio; Clifford Voss (Hydrogeology Journal, 2018)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Detecting inter-aquifer leakage in areas with limited data using hydraulics and multiple environmental tracers, including 4He, 36Cl/Cl, 14C and 87Sr/86Sr - Stacey C. Priestley; Daniel L. Wohling; Mark N. Keppel; Vincent E. A. Post; Andrew J. Love; Paul Shand; Lina Tyroller; Rolf Kipfer (Hydrogeology Journal, 2017)

Greater temperature sensitivity of plant phenology at colder sites: implications for convergence across northern latitudes - Janet Prevéy; Mark Vellend; Nadja Rüger; Robert D. Hollister; Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Karin Clark; Elisabeth J. Cooper; Bo Elberling; Anna M. Fosaa; Gregory H. R. Henry; et al. (Global Change Biology, 2017)
Warmer temperatures are accelerating the phenology of organisms around the world. Temperature sensitivity of phenology might be greater in colder, higher latitude sites than in warmer regions, in part because small changes in temperature constitute greater relative changes in thermal balance at colder sites. To test this hypothesis, we examined up to 20 years of phenology data for 47 tundra plant species at 18 high‐latitude sites along a climatic gradient. Across all species, the timing of leaf emergence and flowering was more sensitive to a given increase in summer temperature at colder than warmer high‐latitude locations. A similar pattern was seen over time for the flowering phenology of a widespread species, Cassiope tetragona . These are among the first results highlighting differential phenological responses of plants across a climatic gradient and suggest the possibility of convergence in flowering times and therefore an increase in gene flow across latitudes as the climate warms.

Prerequisites for Understanding Climate-Change Impacts on Northern Prairie Wetlands - Michael J. Anteau; Mark T. Wiltermuth; Max Post van der Burg; Aaron T. Pearse (Wetlands, 2016)

Discordant CSF/plasma HIV-1 RNA in patients with unexplained low-level viraemia - Sam Nightingale; Anna Maria Geretti; Apostolos Beloukas; Martin Fisher; Alan Winston; Laura Else; Mark Nelson; Stephen Taylor; Andrew Ustianowski; Jonathan Ainsworth; Richard Gilson; Lewis Haddow; et al. (Journal of NeuroVirology, 2016)

Variation in stability of elk and red deer populations with abiotic and biotic factors at the species‐distribution scale - Farshid S. Ahrestani; William K. Smith; Mark Hebblewhite; Steven Running; Eric Post (Ecology, 2016)
Stability in population dynamics is an emergent property of the interaction between direct and delayed density dependence, the strengths of which vary with environmental covariates. Analysis of variation across populations in the strength of direct and delayed density dependence can reveal variation in stability properties of populations at the species level. We examined the stability properties of 22 elk/red deer populations in a two‐stage analysis. First, we estimated direct and delayed density dependence applying an AR (2) model in a Bayesian hierarchical framework. Second, we plotted the coefficients of direct and delayed density dependence in the Royama parameter plane. We then used a hierarchical approach to test the significance of environmental covariates of direct and delayed density dependence. Three populations exhibited highly stable and convergent dynamics with strong direct, and weak delayed, density dependence. The remaining 19 populations exhibited more complex dynamics characterized by multi‐annual fluctuations. Most (15 of 19) of these exhibited a combination of weak to moderate direct and delayed density dependence. Best‐fit models included environmental covariates in 17 populations (77% of the total). Of these, interannual variation in growing‐season primary productivity and interannual variation in winter temperature were the most common, performing as the best‐fit covariate in six and five populations, respectively. Interannual variation in growing‐season primary productivity was associated with the weakest combination of direct and delayed density dependence, while interannual variation in winter temperature was associated with the strongest combination of direct and delayed density dependence. These results accord with a classic theoretical prediction that environmental variability should weaken population stability. They furthermore suggest that two forms of environmental variability, one related to forage resources and the other related to abiotic conditions, both reduce stability, but in opposing fashion: one through weakened direct density dependence and the other through strengthened delayed density dependence. Importantly, however, no single abiotic or biotic environmental factor emerged as generally predictive of the strengths of direct or delayed density dependence, nor of the stability properties emerging from their interaction. Our results emphasize the challenges inherent to ascribing primacy to drivers of such parameters at the species level and distribution scale.

Glyoxalase-1 overexpression partially prevents diabetes-induced impaired arteriogenesis in a rat hindlimb ligation model - Olaf Brouwers; Liang Yu; Petra Niessen; Jos Slenter; Karolien Jaspers; Allard Wagenaar; Mark Post; Toshio Miyata; Walter Backes; Coen Stehouwer; Maya Huijberts; Casper Schalkwijk (Glycoconjugate Journal, 2016)

A cloud-based spatial-temporal inventory for sustainable urban soil management - Latoisha Y. Green; Elena A. Mikhailova; Christopher J. Post; Christophe C. J. G. Darnault; William C. Bridges; Mark A. Schlautman (Urban Ecosystems, 2016)

Erratum to: CXCL1 promotes arteriogenesis through enhanced monocyte recruitment into the peri-collateral space - Mark H. M. Vries; Allard Wagenaar; Sanne E. L. Verbruggen; Daniel G. M. Molin; Ingrid Dijkgraaf; Tilman H. Hackeng; Mark J. Post (Angiogenesis, 2015)

CXCL1 promotes arteriogenesis through enhanced monocyte recruitment into the peri-collateral space - Mark H. M. Vries; Allard Wagenaar; Sanne E. L. Verbruggen; Daniel G. M. Molin; Mark J. Post (Angiogenesis, 2015)

Animal regeneration and microbial retention of nitrogen along coastal rocky shores - Catherine A. Pfister; Mark A. Altabet; David Post (Ecology, 2014)
Animal contributions to ecosystem productivity via nutrient regeneration are increasingly recognized as significant for ecosystem productivity. The paradigm in coastal upwelling systems, in contrast, remains centered around the idea that nutrient supply is extrinsic and sourced from deep water. Here we tested for both animal contributions to nitrogen regeneration and microbial retention of nitrogen along a gradient of animal abundance in Washington State, USA. Using inferences from the concentration and isotopic composition of nitrogen forms, as well as the stable nitrogen isotopic composition of particulate organic matter, and plant and animal tissue, we found increased ammonium as well as greater stable nitrogen isotope values in these organisms in areas of increased animal abundance. We further tested the effect of the nearshore biota by comparing it with an immediately adjacent offshore area, and found an enriched δ 15 N value for nitrate and particulate organic matter. Further, an analysis of the dual isotopes of δ 15 N and the δ 18 O of nitrate indicated increasing microbial processing in the nearshore. Isoscapes, or the spatial pattern of stable isotopes, revealed that animal and microbial processing of nitrogen leave a consistent signature and are thus a previously overlooked and essential component of nearshore productivity.

Successes and Challenges from Formation to Implementation of Eleven Broad‐Extent Conservation Programs - ERIK A. BEEVER; BRADY J. MATTSSON; MATTHEW J. GERMINO; MAX POST VAN DER BURG; JOHN B. BRADFORD; MARK W. BRUNSON (Conservation Biology, 2014)
Integration of conservation partnerships across geographic, biological, and administrative boundaries is increasingly relevant because drivers of change, such as climate shifts, transcend these boundaries. We explored successes and challenges of established conservation programs that span multiple watersheds and consider both social and ecological concerns. We asked representatives from a diverse set of 11 broad‐extent conservation partnerships in 29 countries 17 questions that pertained to launching and maintaining partnerships for broad‐extent conservation, specifying ultimate management objectives, and implementation and learning. Partnerships invested more funds in implementing conservation actions than any other aspect of conservation, and a program's context (geographic extent, United States vs. other countries, developed vs. developing nation) appeared to substantially affect program approach. Despite early successes of these organizations and benefits of broad‐extent conservation, specific challenges related to uncertainties in scaling up information and to coordination in the face of diverse partner governance structures, conflicting objectives, and vast uncertainties regarding future system dynamics hindered long‐term success, as demonstrated by the focal organizations. Engaging stakeholders, developing conservation measures, and implementing adaptive management were dominant challenges. To inform future research on broad‐extent conservation, we considered several challenges when we developed detailed questions, such as what qualities of broad‐extent partnerships ensure they complement, integrate, and strengthen, rather than replace, local conservation efforts and which adaptive management processes yield actionable conservation strategies that account explicitly for dynamics and uncertainties regarding multiscale governance, environmental conditions, and knowledge of the system? Éxitos y Retos de la Formación a la Implementación de Once Programas de Conservación de Amplio Alcance

Ammonium cycling in the rocky intertidal: Remineralization, removal, and retention - Santhiska Pather; Catherine A. Pfister; David M. Post; Mark A. Altabet (Limnology and Oceanography, 2014)
Rocky intertidal productivity is traditionally thought to be sustained almost solely by upwelled nitrate with remineralized forms of minor importance. Using tidepools as natural experimental mesocosms, we conducted 15 N‐tracer experiments to test whether ammonium remineralized within the rocky intertidal is also a significant source of fixed N to localized ecosystem production. Comparison of tidepools with and without the dominant bivalve Mytilus californianus allowed consideration of its role in NH + 4 cycling. Closed water‐incubation bottles were used to investigate the contribution of suspended microbes to NH + 4 cycling. Tidepools with mussels had both greater NH + 4 remineralization (two times) and NH + 4 removal as compared with those without, with daytime rates greater than nighttime rates. Incorporation of NH + 4 tracer by particulate organic matter and macroalgae, and the persistence of this signal in tidepools for several days following the experiment, showed retention of autochthonous NH + 4 in the system. Remineralization rates were tightly correlated to removal rates when compared over all treatments and experiments, but NH + 4 remineralization was significantly greater than removal, suggesting a surplus available to nearshore primary producers.

Anti-inflammatory M2, but not pro-inflammatory M1 macrophages promote angiogenesis in vivo - Nadine Jetten; Sanne Verbruggen; Marion J. Gijbels; Mark J. Post; Menno P. J. De Winther; Marjo M. P. C. Donners (Angiogenesis, 2014)

The cyanate utilization capacity of marine unicellular Cyanobacteria - Nina A. Kamennaya; Mark Chernihovsky; Anton F. Post (Limnology and Oceanography, 2008)
Cyanate, a by‐product of urea decomposition, is a potential nitrogen (N) source in marine environments, but to date it has received scant attention. Cyanobacteria presumably acquire this compound via a substrate‐specific ABC‐type transporter ( cynABD ), and they convert it to ammonium and carbon dioxide by cyanase ( cynS ) activity. Participation of cyanate utilization genes in N‐stress responses in cyanobacteria has been implied previously, but its ecological context has not been studied. We employed polymerase chain reaction protocols for cynA amplification to examine the potential for cyanate recruitment in the Gulf of Aqaba, northern Red Sea. We also monitored growth of cyanobacterial strains with different cynABDS complements on cyanate‐containing media. We showed that cyanate is utilized as the sole N source by strains with the full gene complement, and residual growth, fed by natural decay of cyanate to ammonium, was observed in strains lacking any of these genes. Natural abundance of cynA products in the oligotrophic Gulf of Aqaba indicates that cyanate constitutes an essential N source for Prochlorococcus , but not for Synechococcus populations. Noncyanobacterial cynA sequences indicate cyanate utilization by a variety of other phototrophic microorganisms. We hypothesize that in stratified water bodies, cyanate utilization is confined to the N‐deplete upper photic zone, where it plays a role in "regenerated" primary production.

Historical land use and soil analysis guiding corridor landscape design - J. Renee Keydoszius; S. Knight Cox; Mary B. Haque; Elena Mikhailova; Christopher J. Post; William C. Stringer; Mark A. Schlautman (Urban Ecosystems, 2007)

Nutrient cycling at the landscape scale: The role of diel foraging migrations by geese at the Bosque del Apache National Wildlife Refuge, New Mexico - James F. Kitchell; Daniel E. Schindler; Brian R. Herwig; David M. Post; Mark H. Olson; Michael Oldham (Limnology and Oceanography, 1999)
Wildlife refuges are sites of dense aggregations of wintering waterfowl. Refuge managers are concerned about local water‐quality effects and the amount of birdborne nutrient load that might cause eutrophication in roosting ponds and(or) be exported to downstream systems. We initiated this research effort to test the hypothesis that daily feeding migrations by geese represented a significant source of nutrients to wetland systems at the Bosque del Apache National Wildlife Refuge in the middle Rio Grande River valley of New Mexico. We documented the role of geese in translocating nutrients through a combination of time budget and mass balance models for birds, bioassays of phytoplankton growth, and stable isotope methods that trace the source of nitrogen to food webs. Geese increased the nutrient loading rates in some wetland ponds by up to 40% for total nitrogen and 75% for total phosphorus. Bioassays revealed that nitrogen was consistently limiting to primary production by algae in the ponds. Chlorophyll levels increased in proportion to bird densities. Fish and crayfish from the ponds intensively used by birds had very low stable nitrogen signatures relative to those from the Rio Grande River. This result derived from the low 15 N in alfalfa and corn, which were the primary forage for birds, and accumulated through food webs in proportion to bird use of individual ponds as roosting areas. In general, the wetland ponds functioned efficiently in retaining the birdborne, allochthonous nutrient load and only modest amounts of the total nitrogen or phosphorus were exported downstream.